ANALISIS PEMELIHARAAN SARANA DAN PRASARANA KANTOR PADA CV KOLABORASI PEMUDA CERDAS - Prastika, Aliefa Cindy; Wolor, Christian Wiradendi; Marsofiyati (LPPM Politeknik Pajajaran ICB Bandung, 2023)
This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews, and documentation, while secondary data was obtained through books, previous research, and articles related to research. The aim of this research is to determine the maintenance of office infrastructure at the CV Kolaborasi Pemuda Cerdas which includes maintenance scheduling, storage, as well as obstacles and solutions in maintaining office infrastructure. From the results of this research, it can be seen that the CV Kolaborasi Pemuda Cerdas office has carried out routine and periodic maintenance, but for the storage of facilities and infrastructure it does not yet have a neat storage system. This can be seen from the lack of special storage warehouses available. Currently, for storing office infrastructure, there is a room in the form of a room which is designed to be a storage room for office equipment.